Measurement plannig of natural purification in artificial water reservoirs - Sopruniuk, A. (Видавництво Львівської політехніки, 2017)
Наведено і описано схему планування вимірювань процесів природного очищення води в штучних водоймах. Схему можна використати для вимірювання якості води в інших водоймах, таких як річки, озера і підземні води, однак об’єкт вимірювань у цій статті чітко визначений. Також розглянуто конкретні чинники впливу на якість води та засоби вимірювань. Описану схему контролю якості води можна використати для інших об’єктів.

The measurement planning process of natural purification in artificial water reservoirs was presented and discussed in the paper. The general scheme of the measurement in reservoirs is similar to water quality assessment in another water bodies like rivers, lakes and groundwater, however in this work the objective of measurements is clearly define. In the paper the specific factors and needs for objective realization were presented. The paper describes measurements planning process and it can be use as the source for measurements preparation.
Keywords: планування вимірювання; природне очищення; штучні водойми; показники води; measurement planning; natural purification; artificial water reservoirs; water indicators; 004.9